2011
DOI: 10.1167/iovs.09-4798
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Elasticity of the Human Cornea

Abstract: The stiffness of the human cornea increases by a factor of approximately two between the ages of 20 and 100 years. This variation is relevant to the algorithms used to predict the response to incisional and ablative refractive surgery and will also affect the formulas used to calculate intraocular pressure by applanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 43 publications
6
86
0
10
Order By: Relevance
“…30 Additionally, recent studies demonstrate clear dependence of ocular tissue elasticity as a function of age. 35 Therefore, higher velocities measured in corneas of older mice suggest that the elasticity of the cornea is increasing with the age.…”
mentioning
confidence: 98%
“…30 Additionally, recent studies demonstrate clear dependence of ocular tissue elasticity as a function of age. 35 Therefore, higher velocities measured in corneas of older mice suggest that the elasticity of the cornea is increasing with the age.…”
mentioning
confidence: 98%
“…Changes in corneal thickness due to ageing, age-related increase of cataracts that leads to myopic changes, and reduction in corneal curvature can be regarded as some of the reasons behind this condition. Different correlations between choroidal thickness and spherical equivalent in different age groups also occur because of these reasons (22). Min Kim et al's study has shown that there is a significant difference between refraction and choroidal thickness in people below the age of 60 while this correlation is not observed in people older than 60 (23).…”
Section: Discussionmentioning
confidence: 99%
“…18 Radial speckle shearing interferometry has been used to show the effect of using different parameters during LASIK surgery such as depth and angles of incisions. 19 It has also been used to determine the changes in Young's modulus of the cornea during ageing 20 and following crosslinking. 21 It is non-contact, nondestructive, provides data in real time, and is highly sensitive; the sensitivity can be optimised so the cornea is loaded at pressures within the physiological range.…”
Section: Laser Interferometrymentioning
confidence: 99%